Mordechai COGAN, Bound for Exile. Israelites and Judeans under Imperial Yoke. Documents from Assyria and Babylonia, A Carta Handbook, Jerusalem 2013, ss. 192. - Chrostowski, Waldemar (Collectanea Theologica, 2017)
recenzja